External Beam Radiotherapy in the Treatment of Gastroenteropancreatic Neuroendocrine Tumours: A Systematic Review. Issue 7 (July 2018) - Chan, D.L.; Thompson, R.; Lam, M.; Pavlakis, N.; Hallet, J.; Law, C.; Singh, S.; Myrehaug, S.
Abstract: Aims: External beam radiotherapy (EBRT) is infrequently used to treat gastroenteropancreatic neuroendocrine tumours (GEPNETS), with little published data to date. We carried out a systematic review to assess the activity of EBRT for GEPNETS. Materials and methods: Major databases were searched for papers including at least five patients treated with contemporary EBRT techniques. Eligible studies underwent dual independent review. The primary end points were response rate for lesions treated with definitive intent and recurrence-free survival for primary lesions treated with neoadjuvant or adjuvant intent. Results: Of 11 included studies (all retrospective), seven investigated pancreatic neuroendocrine tumours (PNETs, 100 patients, 14% grade 3) and four studies investigated extra-pancreatic neuroendocrine tumours (84 patients, 14% grade 3). Trials investigating PNETs administered a median of 50.4 Gy via three-dimensional conformal radiotherapy and intensity-modulated radiotherapy. EBRT was given with neoadjuvant or adjuvant intent in 56 patients, with a recurrence rate of 15%. For the 44 patients not undergoing surgery, the radiological response rate was 46%. Grade 3 + toxicity rates were 11% (acute) and 4% (late). Twelve patients with anorectal neuroendocrine carcinoma received 58 Gy to the primary tumour. Seventy-two patients were treated to sites of metastatic disease (34 bone, 27 brain, 11 soft tissue). Local and distant control were poorly reported. Overall survival ranged from 9 to 19 months. No studies in this group reported toxicity outcomes. Conclusions: There are limited, retrospective data on the overall activity and safety of EBRT in GEPNETS. EBRT generally seems to be well tolerated in selected PNET patients with encouraging activity. Well-designed prospective studies in clearly defined populations are required to clarify the role of EBRT in neuroendocrine tumours. Highlights: EBRT was well tolerated in patients with NET with Grade 3 acute toxicity 11%. Patients undergoing definitive RT for pancreatic NET had a 44% response rate. There are few data regarding efficacy of RT for extra-pancreatic NET.